Anonymity, Efficiency Wages and Technological Progress - Stephen Broadberry; Sayantan Ghosal; Eugenio Proto (Center for Economic Studies and ifo Institute (CESifo), 2016)
Although the Industrial Revolution is often characterized as the culmination of a process of commercialisation, the precise nature of such a link remains unclear. This paper provides an analysis of one such link: the role of commercialisation in raising wages as impersonal labour market transactions replace personalized customary relations. In the presence of an aggregate capital externality, we show that the resulting shift in relative factor prices will, under certain conditions, lead to higher capital-intensity in the production technology and hence, a faster rate of technological progress. We provide historical evidence using European data to show that England was among the most urbanized and the highest wage countries at the onset of the Industrial Revolution. The model highlights the role of the informal sector and migration to urban areas, via their impact on the prevailing level of anonymity within an economy, as a driver of capital accumulation and technological progress in modern developing countries. Unemployment subsidies and cash transfer schemes that may have as a potential negative side effect the increase of employment in the informal sector can lead to increased efficiency wages, capital accumulation and technological progress in the formal sector, while restricting migration to the urban sector can have the opposite effect.
Keywords: N13; O14; O43; 330; commercialization; industrial revolution; anonymity; efficiency wages; learning by doing